Colonization of soft wheat following infection of the stem base by Fusarium culmorum and translocation of deoxynivalenol to the head - Covarelli, Lorenzo; Beccari, G.; Steed, A.; Nicholson, P. (Wiley-Blackwell, 2012)
Following inoculation of the base of soft wheat seedlings with Fusarium culmorum, disease symptoms typical of crown rot developed at the stem base and extended up to the third node by plant maturity. Fungus was isolated from all tissues exhibiting symptoms but not from symptomless tissues. Histopathological analysis revealed that the fungus was present mainly in the parenchymatic cells of the stem base and colonized the tissues via apoplastic and symplastic pathways. Host response in advance of pathogen colonization was observed. At maturity, plants were divided into sections from the inoculated area to the head. Heads were also separated into grain, rachis and chaff components. Colonization by the fungus was assessed by isolation from surface-sterilized segments and quantified by real-time PCR. Disease symptoms and the fungus were detected up to the third node, while deoxynivalenol (DON) was present in all stem segments and heads. Within the head, the DON concentration was higher in the rachis than in the chaff and grain components. These results demonstrate that F. culmorum can extensively colonize stem tissues but not reach the head by the time of plant maturity. In contrast, DON was detected in tissues beyond those colonized by the fungus, translocating to the head where, although accumulating mainly in the rachis, significant quantities accumulated in the grain. These findings indicate that there is a potential threat of contamination of grain with DON where severe crown rot is present in a crop. © 2012 The Authors. Plant Pathology © 2012 BSPP.